Effectiveness of education program on Nurses’ Knowledge about Treatment and Follow-up of Hydatidiform Mole Pregnancy - Kadhom, Hanan Ali; Ali, Rabea Mohsen; Taha, Faiza Ali Nasor (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): the study aimed to evaluate knowledge of nurses about treatment and follow-up of Hydatidiform mole pregnancy, and determine the effectiveness of the education program on nurses' knowledge.Methods: a quasi-experimental design was carried out on nurses who work in gynecological units with the application of pretest and posttest design, the nurses were exposed to pre-test, implementation of education program, post–test one immediately after the application of the program, and post-test two was done after two weeks after the first post-test. The study started from January 17th, 2022 to May 2nd, 2023. Non probability (purposive sample) was selected, the study sample consists of (50) nurses who work in gynecological units of Baghdad hospitals. Validity of the study questionnaire was determined through a panel of (12) experts and the reliability were determined by test-retest approach, the statistical analysis of the data was conducted through the application of descriptive and inferential statistical analysis procedures.Results:  the result revealed that age group 20-less than 26 years of which 56% of nurses with an average age of 26±5 years. The level of nurses’ knowledge about treatment and “follow up of hydatidiform mole pregnancy was poor during the pre-test (Mean score= .32). During the post-test 1 and 2, the nurses show good level of knowledge (Mean score= .98 and .89) in which the mean scores show good level after implementation of the program and confirmed its effectiveness.  Conclusion: The study confirmed the effectiveness of the education program on nurses’ knowledge about treatment and follow-up of Hydatidiform mole pregnancyRecommendations: to improve the nursing role in patient care, It is important to design a booklet, and flex about treatment and follow-up care about molar pregnancy for nurses. The establishment of short workshops involves lecture about hydatidiform mole. Encouraging the Ministry of Higher Education to improve and develop educational curricula Further studies can be conducted on wide range variable.